Spol in nadljudje v ameriški znanstveni fantastiki: od cisspolnih supermož do transspolnih superjunakinj - Šporčič, Anamarija (Vestnik za tuje jezike, 2024)
The article provides a concise overview of how the Darwinian genesis of the superhero science fic-tion genre and the entrenched binary gender representations, patriarchal patterns, and hierarchies delayed the emergence of transgender superheroes. It also, however, proposes that the very rigidity of the genre and its tropes eventually enabled subversive portrayals of superheroes, initially in a eminist and later in a transgender context. Science fiction is still often perceived as a predomi-nantly male genre, which is particularly evident in the subgenre of superhero stories that present traditional masculine traits as superior. Despite the theoretically limitless possibilities of the genre for exploration, questioning, and experimentation free from societal expectations, an analysis of the history of gender representation in science fiction reveals that it often not only reflects the societal norms of its time but may even be more conservative. Women in superhero stories have historically been marginalized and depicted primarily as sidekicks or sexual objects, rarely exhib-iting powers or roles equal to those of male superheroes. Early female characters in science fiction were mainly portrayed as threats or objects of desire. Female superheroes emerged slowly and were often portrayed from a male perspective, reinforcing patriarchal norms. The rise of feminist science fiction in the 1960s and 1970s brought about the first radical reinterpretations of gender, but it is only from the 1990s onwards that we observe greater diversity and inclusion within the genre, including of transgender characters. A brief overview of existing transgender superheroes including the strengths and weaknesses of their portrayals is followed by an analysis of the young adult novel Dreadnought (2017) by April Daniels, serving as a representative example of a trans-gender experience presented through the subversion of the superhero archetype.
Keywords: April Daniels; Dreadnought; Dreadnought, April Daniels; gender identity; science fiction; spolna identiteta; transgender superheroes; transspolni superjunaki; znanstvena fantastika